1999
DOI: 10.1002/(sici)1522-2586(199910)10:4<563::aid-jmri9>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coronary flow reserve with fast cine phase contrast magnetic resonance imaging: Comparison with measurement by Doppler guide wire

Abstract: Fast cine phase contrast magnetic resonance imaging (fast cine phase contrast MRI) can measure phasic coronary flow velocity in humans. The purpose of this study was to compare the coronary flow velocity reserves measured by MR IMAGING with those obtained by Doppler guide wire. Nineteen patients with ischemic or valvular heart disease were studied. Fast cine phase contrast MR images of the left anterior descending (LAD) artery were acquired during breath‐hold time in the basal state and after administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…This observation has also been reported from other authors. 19,29,30 It can be mainly attributed to the lower temporal resolution (and, thus, the highest flow velocity during the cardiac cycle is missed) and the lower spatial resolution (and, thus, an average flow velocity of a small region of interest, rather than the fastest flow velocity within the vessel, is determined) compared with intravascular Doppler. However, underestimation was systematic and thus can be corrected for.…”
Section: Discussionmentioning
confidence: 95%
“…This observation has also been reported from other authors. 19,29,30 It can be mainly attributed to the lower temporal resolution (and, thus, the highest flow velocity during the cardiac cycle is missed) and the lower spatial resolution (and, thus, an average flow velocity of a small region of interest, rather than the fastest flow velocity within the vessel, is determined) compared with intravascular Doppler. However, underestimation was systematic and thus can be corrected for.…”
Section: Discussionmentioning
confidence: 95%
“…Correction for the through-plane motion of the vessel itself is generally performed by subtracting the velocity of an area of adjacent myocardium. For the left coronary artery, this results in the expected diastolic flow predominance [58]. Although studies have reported reasonably good correlations (r=0.7-0.9) between MR and Doppler data, breath-hold segmented FLASH underestimates velocities, with values being typically only 30-40% of those measured by Doppler [58,59].…”
Section: Coronary Artery Blood Flow (Cbf)mentioning
confidence: 99%
“…For the left coronary artery, this results in the expected diastolic flow predominance [58]. Although studies have reported reasonably good correlations (r=0.7-0.9) between MR and Doppler data, breath-hold segmented FLASH underestimates velocities, with values being typically only 30-40% of those measured by Doppler [58,59]. Reducing the acquisition window increases accuracy [59] (Fig.…”
Section: Coronary Artery Blood Flow (Cbf)mentioning
confidence: 99%
“…The first is epicardial coronary stenosis [1][2][3][4][5][6][7][8] and the second is disturbance of the microcirculation. [9][10][11][12][13][14] In this study, all patients underwent coronary angiography and the absence of angiographically significant coronary stenosis was verified.…”
Section: Difference In the Impairment Of Vasodilatation Capacitymentioning
confidence: 71%
“…[1][2][3][4][5][6][7][8] Therefore, the MFR value is clinically useful for decision-making and the strategy of coronary intervention. Recent studies have shown that MFR is impaired by age 9 and coronary risk factors, such as smoking, 10 hyperlipidemia (HPL), 11,12 diabetes mellitus (DM), 13 and hypertension (HTN), 14 even in the absence of coronary stenosis.…”
mentioning
confidence: 72%